2021
DOI: 10.1111/cen.14573
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cortisol levels by continuous positive airway pressure in patients with obstructive sleep apnoea: Meta‐analysis of 637 individuals

Abstract: Background: Obesity, obstructive sleep apnoea (OSA) and hypertension frequently coexist and are associated with elevated cortisol levels. Identification and treatment of such patients is important when investigating for suspected Cushing's syndrome and hypertension. Studies of the impact of continuous positive airway pressure (CPAP) on cortisol and blood pressure are limited by the small sample size and show conflicting findings. We conducted a meta-analysis to document changes in the levels of cortisol and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In a meta-analysis of 637 participants with OSA, CPAP treatment significantly reduced both plasma and salivary cortisol levels. Individuals undergoing investigation for Cushing’s syndrome would benefit from an initial screening for OSA; the impact of CPAP on cortisol has been debatable because of conflicting findings between studies due to small sample sizes [ 7 ]. The mechanism of correlation between sleep apnea and Cushing’s disease/Cushing’s syndrome have never been investigated; it has been suggested that weight gain and adipose tissue accumulation according to a centripetal pattern in the subcutaneous tissue of the neck can likely lead to the development of obstructive sleep apnea in these patient population.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 637 participants with OSA, CPAP treatment significantly reduced both plasma and salivary cortisol levels. Individuals undergoing investigation for Cushing’s syndrome would benefit from an initial screening for OSA; the impact of CPAP on cortisol has been debatable because of conflicting findings between studies due to small sample sizes [ 7 ]. The mechanism of correlation between sleep apnea and Cushing’s disease/Cushing’s syndrome have never been investigated; it has been suggested that weight gain and adipose tissue accumulation according to a centripetal pattern in the subcutaneous tissue of the neck can likely lead to the development of obstructive sleep apnea in these patient population.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although there was no significant difference in the BMI within the two groups, some of the patients in the unsuppressed PRA group exhbited a higher BMI that could lead to sleep apnea syndrome (SAS). SAS could, in turn, lead to the elevation of PRA and cortisol levels via dysregulation of the renin-angiotensin-aldosterone system through altered sympathetic nervous system activation [ 56 , 57 ]. Actually, some patients in the unsuppressed PRA group showed a high apnea-hypo index, as shown in S1 Table .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is a plausible that CPAP has no effect on circulating testosterone levels, which if true would point to irreversible neuroendocrine changes to the testicular axis arising from longstanding intermittent hypoxia – irreversible changes that are not found in the adrenal axis. By comparison, a meta-analysis of 22 studies (of which 6 were randomized controlled trials) was sufficiently powered to conclude that CPAP decreases cortisol [ 122 ]. More studies, including randomized sham-controlled studies utilizing repetitive overnight or 24-h blood sampling and modern mathematical deconvolution techniques that better discriminate subtle regulatory changes are needed to finally resolve this issue.…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%